Penerapan lean manufacturing untuk meningkatkan kinerja procurement dengan analisa performance supplier pada kasus industri baja - Muhammad Zuhdi Prasetyo Nugroho (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
The steel industry is classified as a strategic industry that supports many industries, due to continuous national development. The steel industry must improve the quality of its production processes in order to increase its competiveness. One factor that supports the stability of the production process is the procurement process. To overcome the problem, the TOPSIS method is used to analyze supplier performance as a basis for determining supplier selection during the procurement process. Data is taken from the results of the questionnaire from the Material Procurement Division and the Vendor Management Office with criteria of price, quality, delivery time, suitability of the goods and Supplier Professionalism, and by choosing five alternative suppliers who are active in supplying goods. From the results of the questionnaire created a normalized matrix. Form the matrix determined distance with positive solution and negative solution alternative so we get a preference value for each alternative, and obtained PT. Siemen as a supplier with the closest relative proximity with a value of 0.6469.